Prácticas higiénico-sanitarias: factores contaminantes de los depósitos de agua en el sector «Pianguapi», Esmeraldas, Ecuador - Piguave Reyes , José Manuel (2024)
"Introduction: water is an essential resource of public health and environmental importance that governs the life of communities and civilizations. Currently, the contamination of water in its various sources such as the overflow of liquids at the household level, agricultural and livestock work, and the lack of a sewage system in the communities allow the contamination of supplies to originate. Methodology: an observational, analytical, cross-sectional study was carried out on 50 families, selected through simple random probability sampling using a hygienic-sanitary inspection form. Results: according to the results obtained, 100 % of the participating families find themselves in the need to store drinking water due to the non-continuity in the distribution process from the main network and risk practices adopted in the community that contribute to the contamination of the reservoirs were determined, because 36 % carry out annual cleanings. 38 % and 52 % do not cover or partially cover the container, 36 % keep them dirty and 70 % use jugs for intra-household distribution, in addition to the environmental effects due to a high use of latrines and lack of connection to the sewer network, coupled with this with 14 % of families burying garbage. Conclusions: the hygienic-sanitary practices that are evidenced in this sector contribute to the contamination and poor storage of water, which generates a public health problem due to the risk of suffering diseases from its consumption and use, evidencing the need for intervention in terms of prevention and health promotion in safe water issues"